The Christian roots of critique. How Foucault's confessions of the flesh sheds new light on the concept of freedom and the genealogy of the modern critical attitude - Schubert, Karsten (2021)
Abstract: Finally published 34 years after his death, Foucault's book Confessions of the Flesh sheds new light on the debate about freedom and power that shaped the reception of his works. Many contributors to this debate argue that Foucault's theory of power did not allow for freedom in the 'genealogical phase,' but that he corrected himself and presented a solution to the problem of freedom in his later works, especially through his reflection on ancient ethics and technologies of the self in volumes two and three of History of Sexuality, as well as the concept of parrhesia. In contrast to this view, I argue that Confessions of the Flesh shows that a concept of freedom as self-critical hermeneutics that aims at identifying a foreign power within the subject was only developed in Foucault's analysis of Christian practices of penance and confession. This interpretation of Confessions of the Flesh opens a new field of inquiry into the genealogy of critique and both the repressive and emancipative effects of truth-telling and juridification